Influence of relationship quality and severity of aggression on post-conflict affiliation in Hamadryas Baboons (Papio hamadryas hamadryas). - Lau, Weng Yi. (2009)
We examined two forms of post-conflict affiliation, reconciliation and third-party affiliation (TPA), in hamadryas baboons (Papio hamadryas hamadryas), and investigated the influence of relationship quality and severity of aggression on the occurrence of reconciliation and TPA. Using the amount of time spent in proximity between pairs of hamadryas baboons as an index of relationship quality, we found that relationship quality was positively correlated with the frequency of reconciliation. This provides further evidence that relationship quality influences the likelihood of reconciliation between former opponents. We also found that relationship quality was negatively correlated but statistically non-significant with the frequency of TPA. Finally, we found that severity of aggression did not influence the occurrence of reconciliation and TPA.